Cyber security maturity model and Maqasid al-Shari'ah - M. Ridza, Nadwiyah; Abdul Aziz, Normaziah; Saidin, Aznan Zuhid; Wahiddin, Mohamed Ridza; Ahmad Dahlan, Abdul Rahman; Ibrahim, Jamaludin; Ahmad H.Osman, Rahmah (Institute of Electrical and Electronics Engineers Inc., 2018)
Knowing how vulnerable an organisation or a state towards cyberattacks, is referred to as Cyber security Index or Maturity Level. Such an index is important to evaluate the organisation's level of vulnerability to cyber threats. Various cyber security models are initiated and applied across the globe as tools towards measuring the mentioned index. These models provide indicators as to how ready an organisation or a country react to attacks and what are the steps to be taken to alleviate the situation. On the other hand, the Maqasid Al-Shari'ah or the higher objectives of Shari'ah generally seeks to preserve the five essentials in human life: faith (deen), life (nafs), intellect ('aql), progeny (nasl) and wealth (mal). This work is proposing the use of Maqasid Al-Shari'ah to identify and prioritizes critical incidents that need to be addressed to ensure the continuity of civil society from the Islamic perspective. This research will also deliver a prototype tool that captures users' input on an organisation's profile and displays the corresponding measured cyber security maturity level of the organisation.